Perlindungan Hak Informasi Warga Negara Indonesia Dalam Pemilu 2024 Dikaitkan Dengan Problematika ‘Sirekap’ Sebagai Sarana Informasi Alternatif - Alpha Pratama Andriansyah; Azzahra Herawati; Bilkis Nabila; Muhammad Reza Ilham; Muhammad Wildan Fathurrohman; Rizky Mulya (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine and analyze the urgency of Sirekap in calculating alternatives for 2024 election and the problems in recapitulating votes for the 2024 election using Sirekap and also how to solve the problems in recapitulating votes using Sirekap. This research uses normative juridical research methods, research by browse or ready-to-use document materials. This research uses primary legal materials, namely legal materials originating from statutory regulations, such as Undang-Undang Dasar 1945, PKPU No. 25 Tahun 2023 Tentang Pemungutan dan Perhitungan Suara dalam Pemilihan Umum, but also utilizing secondary legal materials such as relevant journals and books as well as tertiary legal materials in the form of data and facts from the internet. The research results show that the use of Sirekap in the 2024 election is faced with a number of challenges and obstacles that need to be solve. One of the main challenges is data and system hacking, which could threaten the integrity and validity of election results. Apart from that, the lack of transparency in the use of Sirekap is also a major concern. The solution uses a blockchain base that can identify and provide identity security for people who use Sirekap, blockchain technology also provides a high level of security. It is hoped that the application of blockchain technology can be an option for solving various problems, especially in the 2024 election process which is direct, free, confidential, honest and fair. However, implementing blockchain technology for elections requires attention to security, regulatory, operational and broad technology adoption challenges.